GM1 Gangliosidosis, Late Infantile Onset Dystonia, and T2 Hypointensity in the Globus Pallidus and Substantia Nigra - Vieira, JP (2013)
BACKGROUND: GM1 gangliosidosis is a rare disease due to mutations in the GLB1 gene and autosomal recessive deficiency of b-galactosidase. There is considerable overlap between classical phenotypes and clinical and imaging findings, which are often difficult to interpret. PATIENT: The patient in this study had dysmorphism, dysostosis, progressive dystonia, and T2 hypointensity in the basal ganglia. Partially similar clinical and radiologic findings were described previously in two reports. CONCLUSIONS: T2 hypointensity in the globus pallidus should, in the appropriate clinical setting, lead to consideration of thediagnosis of GM1 gangliosidosis.